Fire Alarm System Alert Via Short Message Service (SMS) - Muhammad Zulhimi Hussin; Jamaludin Jalani; Jumadi Abdul Sukor; Muhammad Irfan Rahimi; Ramlah Awang; Noorhamizah Mohamed Nasir (International Journal of Integrated Engineering, 2026)
This paper presents a low-cost fire alarm alert system that integrates a smoke sensor, a flame sensor, and a GSM module to provide both local audible warning and remote notification via Short Message Service (SMS). The prototype was implemented using an Arduino Uno and was designed to reduce false alarms by requiring dual-sensor validation before triggering an alert. Experimental testing was conducted to evaluate sensor response versus distance and installation orientation. For smoke detection, the system was configured to trigger when the smoke sensor output exceeded 300 bits, where vertical sensor placement produced higher readings than horizontal placement and achieved the threshold at approximately 45 cm. For flame detection, the alarm condition was defined as a flame sensor output below 1000 bits, and the prototype reliably detected flame up to approximately 45 cm, with minor differences between horizontal and vertical orientations. GSM performance tests showed that the SMS alert was delivered within 5–6 seconds, where Celcom achieved the fastest and most consistent delivery time (5 s) compared to Digi and Maxis (6 s). Overall, the results confirm that the proposed system can provide timely fire alerts and stable sensor triggering behavior under short-range indoor test conditions, supporting its suitability as an affordable early-warning prototype for residential applications.